2017
DOI: 10.1158/0008-5472.can-16-2098
|View full text |Cite
|
Sign up to set email alerts
|

The p53/p21 Complex Regulates Cancer Cell Invasion and Apoptosis by Targeting Bcl-2 Family Proteins

Abstract: The tumor suppressor p53 binds prosurvival Bcl-2 family proteins such as Bcl-w and Bcl-X L to liberate Bax, which in turn exerts proapoptotic or anti-invasive functions depending on stress context. On the basis of our previous finding that p53 interacts with p21, we investigated the possible involvement of p21 in these functions. Here, we report that although p53 can bind Bcl-w alone, it requires p21 to liberate Bax to suppress cell invasion and promote cell death. p21 bound Bcl-w, forming a p53/p21/Bcl-w comp… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
106
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 169 publications
(114 citation statements)
references
References 39 publications
(53 reference statements)
7
106
1
Order By: Relevance
“…Simultaneously, nuclear p53 augments the pool of BAX molecules via executing transcription of BAX 147 . The inhibitory role of p21 in the regulation of BCL-w-dependent lung cancer, colon cancer, and neuroblastoma cell invasion has been demonstrated in addition to p53 149 . Although p53 and p21 can bind to BCL-w independently, the triple p53/p21/BCL-w complex is required for BAX release from BCL-w and suppression of cell invasion (Fig.…”
Section: Role Of Bcl-w In Migratory and Invasive Potentials Of Cancermentioning
confidence: 99%
See 1 more Smart Citation
“…Simultaneously, nuclear p53 augments the pool of BAX molecules via executing transcription of BAX 147 . The inhibitory role of p21 in the regulation of BCL-w-dependent lung cancer, colon cancer, and neuroblastoma cell invasion has been demonstrated in addition to p53 149 . Although p53 and p21 can bind to BCL-w independently, the triple p53/p21/BCL-w complex is required for BAX release from BCL-w and suppression of cell invasion (Fig.…”
Section: Role Of Bcl-w In Migratory and Invasive Potentials Of Cancermentioning
confidence: 99%
“…Although p53 and p21 can bind to BCL-w independently, the triple p53/p21/BCL-w complex is required for BAX release from BCL-w and suppression of cell invasion (Fig. 3) 149 .…”
Section: Role Of Bcl-w In Migratory and Invasive Potentials Of Cancermentioning
confidence: 99%
“…This assumption is corroborated by the observed decrease in ΔΨm, a wallmark in p53 mediated induction of apoptosis. For cell cycle arrest, p53 exerts its effects through cyclin-dependent kinase (CDK) inhibitor p21, leading to cell cycle arrest (Kim et al, 2017). Cell cycle analysis showed that PSC-hex induced cell cycle arrest at the G2/M phase, suggesting a blockage of cell proliferation of the HCT116 wt , which might be regulated by p53 by activating p21.…”
Section: Intrinsic Signaling Pathway Modulated Apoptosis In Hct116 Wtmentioning
confidence: 99%
“…p53 causes apoptosis via regulating the expression, cellular localization, and activity of key effectors of the apoptotic process . p21, a well‐described transcriptional target of p53, regulates cell invasion and death by targeting Bcl‐2 proteins through forming p53/p21 complex . While the pro‐apoptotic Bax gene is a direct target of p53, the overexpression of p53 in p53‐null cells diminish Bcl‐2 expression .…”
Section: Discussionmentioning
confidence: 99%